The Effect Of Hyperbaric Therapy On The Quality Of Life Of Diabetic Foot Ulcers Patients - Wiratama, Rahardyan Dika; Abdul Muhith; Siti Nur Hasina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Diabetes mellitus (DM) is a metabolic disease condition characterized by increased blood sugar levels or hyperglycemia. Uncontrolled diabetes mellitus can cause complications such as diabetic neuropathy (nerve damage), stroke, blindness, and diabetic ulcers (wounds that are difficult to heal). This study aims to determine the effect of hyperbarics on the quality of life of diabetic foot ulcer sufferers. This research uses a quasi-experimental design with a non-equivalent Control Group Design where an intervention group and a control group are selected and then pre- and post-tests are carried out. The sample was 27 people with diabetes. The instrument used is (WHOQOL-BREF). Data analysis used the analysis technique used was Wilcoxon and Mann Whitney. on the post test. The results showed that the average pre-test score for the quality of life of respondents was in the low category, namely the physical domain 68 people (97.1%), the psychological domain 67 people (95.7%), the social domain 54 people (77.1%), and environmental domain 62 people (88.6%). The p value obtained for the physical domain was 0.00 (p<0.05), for the psychological domain 0.012 (p<0.05), for the social domain 0.003 (p<0.05), and for the environmental domain 0.001 (p<0, 05). It can be concluded that there is a significant difference between the patient's quality of life before and after hyperbaric therapy according to the physical, psychological, social and environmental health domains, and there is an influence of hyperbaric therapy on the patient's quality of life.